A Relative Computable Study of Modern Big Data Clustering Procedures for Fair Division - Baby Kala, N; Ramya, S (International Journal of Computer Sciences and Engineering, 2025)
The cordiality business is one of the data-rich enterprises that gets tremendous Volumes of data gushing at high Velocity with extensively Variety, Veracity, and Variability. These properties make the data examination in the cordiality business a big data issue. Meeting the clients' desires is a key factor in the neighborliness business to get a handle on the clients' dependability. To accomplish this objective, advertising experts in this industry effectively search for approaches to use their data in the most ideal way and propel their data scientific arrangements, for example, distinguishing an extraordinary market division clustering and building up a proposal framework. In this paper, we introduce an exhaustive writing audit of existing big data clustering calculations and their favorable circumstances and disservices for different utilize cases. We execute the current big data clustering calculations and give a quantitative correlation of the execution of various clustering calculations for various situations. We additionally display our experiences and proposals with respect to the appropriateness of various big data clustering calculations for various utilize cases. These suggestions will be useful for hoteliers in choosing the proper market division clustering calculation for various clustering datasets to enhance the client encounter and boost the lodging income.